Requirements and effectiveness of distance education in primary schools in Abha during the Corona pandemic from the point of view of educational supervisors and school leaders - Abdelkader, Mahmoud Helal (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effectiveness of distance learning in the primary stage during the Corona pandemic from the point of view of educational supervisors and school leaders. A sample of (23) including (15) primary school leaders, and (18) educational supervisors in Abha city. The results showed that the tool as a whole obtained a total average of (231.41), with a percentage of (47.71); That is, with a medium effectiveness, and the average dimensions ranged between (47.5), with a percentage of (10.09) to (6.12) with a percentage of (20.4), and all of them with a low degree of effectiveness, and based on the results, the researcher recommended some recommendations, including: Holding training courses for teachers and students to develop learning skills about After, forming a positive attitude in the students; To enhance the e-learning culture, educate students not to be occupied with other sites during e-learning, in addition to proposals for complementary studies on a subject.